Influence of agrochemicals fipronil and imidacloprid on the learning behavior of Apis mellifera L. honeybees - doi: 10.4025/actascianimsci.v35i4.18683 - Marcela Pedraza Carrillo; Thaís de Souza Bovi; Adriana Fava Negrão; Ricardo de Oliveira Orsi (Acta Scientiarum. Animal Sciences, 2013)
Agrochemicals on crop cultivated areas is a source of contamination for bees and may causephysiological and behavioral disorders and mortality. The LD50 of the pesticides fipronil and imidaclopridwas determined and their effect on the learning behavior of Apis mellifera L. honeybee evaluated. LD50 wasdetermined by the ingestion of contaminated food with different concentrations of insecticideconcentrations: Fipronil (0, 0.8, 0.4, 0.2, 0.1 and 0.05 μg bee-1) and imidacloprid (0, 0.4, 0.2, 0.1, 0.05 and0.025 μg bee-1). The method of proboscis extension reflection (PER) and learning through citral odorevaluated their responses to food stimulation. LD50 obtained were 0.28 ± 0.11 and 0.10 ± 0.04 μg bee-1 forfipronil and imidacloprid, respectively. The PER test showed no significant difference (p < 0.05) althoughagrochemicals affected the learning of bees. Insecticides fipronil and imidacloprid are extremely harmful toforaging Africanized Apis mellifera bees.